The Effect of Service Quality In Shaping Consumer Purchase Intention With Positive Perception As A Mediating Variable (Study In CitraGarden City Jakarta) - Tony Ngadimun; Teofilus Teofilus; Endi Sarwoko (Dinasti International Journal of Education Management And Social Science, 2024)
The aim of this research is to investigate how the service quality of a product influences consumer purchase intentions through positive perceptions as a mediator. The research aims to understand whether consumers tend to buy a product because they have a positive perception of the quality of the service provided, and how this positive perception mediates the relationship between service quality and purchase intention. In this context, "positive perception" can include consumers' views or evaluations of various aspects of the product, such as reliability, speed of service, responsiveness to customer needs, ease of use, and so on. Meanwhile, "purchase intention" reflects the consumer's tendency or willingness to buy the product within a certain time period. By using mediating variables, this research seeks to explore the mechanisms underlying how service quality influences purchase intentions through its influence on positive perceptions. With a deeper understanding of these factors, companies can improve their marketing and service strategies to more effectively influence consumer purchasing behavior. This research was conducted on consumers who had purchased products with a total of 168 consumers from various domiciles including: North Jakarta, West Jakarta, Central Jakarta, Tangerang, and other domiciles. This research uses descriptive quantitative methods because of clear measurement of the variables directly involved, in-depth statistical analysis, generalization of results to represent a wider population, making it possible to make generalizations about the relationship between the observed variables so that the research results can be more relevant in general. general, and the objectivity of the data collected is numerical and the analysis uses established statistical techniques so as to help reduce subjective bias in the interpretation of results. The research results show that the quality of consumer service has an influence in forming consumer purchase intentions with positive perceptions.